446. Leveraging Partnerships to Care for Babies Born to Mothers after Maternal Zika Infection—US Virgin Islands (USVI). (26th November 2018) - Hunte-Ceasar, Tai; Hillman, Braeanna; Prosper, Andra; Petersen, Derval; Cato, Shana; Davis, Michelle; Fehrenbach, Nicole; Ellis, Esther
Abstract: Background: Since February 2016, the US Virgin Islands Department of Health (VIDOH) has been monitoring the Zika outbreak and its effects on maternal and child health. As of March 19, 2018, the territory reported 291 women with confirmed laboratory evidence of Zika virus during pregnancy. Residents had limited access to the recommended pediatric screenings and specialty services related to Zika virus disease. VIDOH requested technical assistance from Centers for Disease Control and Prevention, Health Resources and Services Administration, Family Voices, and American Academy of Pediatrics to provide these services in the USVI in March 2018. Methods: VIDOH staff called 291 mothers, connected with 148, and scheduled 114 appointments. The clinic set-up included: two intake, four neurology, threeophthalmology, one audiology, one developmental, child life team, and two exit stations. Infants received comprehensive neurology, developmental, ophthalmology, and audiology examinations and were connected to resources such as Infant and Toddlers: Early Intervention services, Act Early: Learn the Signs, Disability Rights of the Virgin Islands and local specialized physicians. A data abstraction team of six reviewed charts for accuracy and abstracted data into both the US Zika pregnancy registry forms and the local Zika database. Results: The visiting specialists evaluated 88 infants; 65 (73.9%) in St. Thomas and 23 (26.1%) in St. Croix, 84 (73.7%) appointments and four walk-ins. There were 53 (60.2%) males and 35 (39.8%) females. Seven (7.9%) infants were 0–2 months, 18 (20.5%) were 3–6 months, 38 (43.2%) were 7–12 months, 25 (28.4%) were 13–24 months. Fifty-eight (65.9%) infants were referred for further follow-up; 35 (60.3%) to an audiologist, 20 (34.5%) to Infants and Toddlers program, 11 (19%) to a neurologist, 10 (17.2%) to an ophthalmologist, 8 (13.8%) to a developmental pediatrician, 8 (13.8%) for physical therapy, four (6.9%) for speech therapy, three(5.2%) for neuroimaging, three(5.2%) for occupational therapy, and 2 (3.4%) to an otorhinolaryngologists. Conclusion: Probable hearing loss was the chief finding in many of the infants screened. Further evaluation on these infants has been recommended based on clinical guidance for infants exposed to Zika virus infection. This can help to identify the types of hearing loss associated with Zika infection in utero . Disclosures: All authors: No reported disclosures.